The year's best science fiction : thirty-first annual collection - Dozois, Gardner R. (New York : St. Martin's Griffin, 2014)
"In the new millennium, what secrets lay beyond the far reaches of the universe? What mysteries belie the truths we once held to be self evident? The world of science fiction has long been a porthole into the realities of tomorrow, blurring the line between life and art. Now, in The Year's Best Science Fiction: Thirty-First Annual Collection the very best SF authors explore ideas of a new world in the year's best short stories"--
One / Nancy Kress -- Murder on the Aldrin Express / Martin L. Shoemaker -- Biographical fragments of the life of Julian Prince / Jake Kerr -- The plague / Ken Liu -- Fleet / Sandra McDonald --The she-wolf's hidden grin / Michael Swanwick -- Bad day on Boscobel / Alexander Jablokov -- The Irish astronaut / Val Nolan-- The other gun / Neal Asher -- Only human / Lavie Tidhar --Entangled / Ian R. MacLeod -- Earth / Stephen Baxter --Technarion / Sean McMullen -- Finders / Melissa Scott -- The Queen of Night's aria / Ian McDonald -- Hard stars / Brenda DuBois -- The promise of space / James Patrick Kelly -- Quicken / Damien Broderick.
Keywords: Science fiction; Short stories; FICTION -- Short Stories. -- Short Stories; FICTION -- Anthologies (multiple authors); Science fiction